High‐throughput sequencing provides insight into manipulated soil fungal community structure and diversity during temperate forest restoration. (4th March 2020) - Lance, Andrew C.; Burke, David J.; Hausman, Constance E.; Burns, Jean H.
Abstract : The process of community assembly in fungal communities is poorly understood and may have important implications for restoration. However, there is a shortage of data describing fungal community composition at various stages of restoration. This study describes how microbial inoculation with field‐collected soils or a commercial inoculum influenced fungal communities during temperate tree restoration. We utilized Illumina Mi‐Seq sequencing technology to examine fungal community structure in the rhizosphere soils of trees at the conclusion of one growing season. Inoculation treatment was found to be a significant determinant of fungal community structure in one of our three experimental tree species ( Liriodendron tulipifera ). We also found a marginally significant influence of inoculation method on fungal community structure in the rhizosphere soils of Quercus rubra, an ectomycorrhizal tree species. Importantly, within these taxa, the use of commercial inocula, while failing to lead to detectable abundances of the inoculated taxa, strongly influenced the resulting fungal community structure after 4 months in the field, relative to control trees that received no such inoculation. We observed lower abundances of Hebeloma, a potentially important ectomycorrhizal genera, in Quercus trees receiving the commercial inoculum compared with control trees; thus, the commercial inoculum might have unexpected consequences for fungal community assembly. Such unintended legacy effects of soil inoculation should be considered in ecological restoration. Furthermore, by taking a time series approach to sampling, high‐throughput sequencing approaches could be used to test the principles of ecological assembly theory, including legacy effects of taxa no longer detectable in the community.